Let's complete the process of solving the equation step by step. The original equation is:
\[ 14r + 14 - 7r = 5r + 8 \]
Step 1: Combine like terms on the left side of the equation.
Combine \(14r\) and \(-7r\):
\[ (14r - 7r) + 14 = 5r + 8 \]
This simplifies to:
\[ 7r + 14 = 5r + 8 \]
Step 2: Subtract \(5r\) from both sides.
Next, subtract \(5r\) from both sides to isolate the terms related to \(r\):
\[ 7r - 5r + 14 = 8 \]
This simplifies to:
\[ 2r + 14 = 8 \]
Step 3: Subtract 14 from both sides.
Now, subtract \(14\) from both sides:
\[ 2r + 14 - 14 = 8 - 14 \]
This simplifies to:
\[ 2r = -6 \]
Step 4: Divide both sides by 2.
Next, divide both sides by \(2\) to solve for \(r\):
\[ r = \frac{-6}{2} \]
This simplifies to:
\[ r = -3 \]
Summary:
Thus, the solutions can be summarized as follows:
- Original equation: \(14r + 14 - 7r = 5r + 8\)
- Combine like terms: \(7r + 14 = 5r + 8\)
- Subtract \(5r\) from both sides: \(2r + 14 = 8\)
- Subtract \(14\) from both sides: \(2r = -6\)
- Divide both sides by \(2\): \(r = -3\)
Final Answer:
\(r = -3\)